2004
DOI: 10.1152/ajprenal.00316.2003
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3decreases podocyte loss and podocyte hypertrophy in the subtotally nephrectomized rat

Abstract: 1,25(OH)(2)D(3) has antiproliferative effects and promotes cell differentiation. This consideration has provided the rationale for studies in subtotally nephrectomized rats showing that 1,25(OH)(2)D(3) interfered with glomerulosclerosis. The cellular mechanisms involved have remained obscure, however. It was the purpose of the present study to assess glomerular structure and cellular composition in subtotally nephrectomized (SNX) rats treated with nonpharmacological doses of 1,25(OH)(2)D(3). Male Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
150
2
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(171 citation statements)
references
References 50 publications
(56 reference statements)
12
150
2
7
Order By: Relevance
“…Recent reports indicate that 1,25(OH)2D3 can alleviate podocyte loss and inhibit podocyte hypertrophy in subtotally nephrectomized (SNX) rats (10). These results clearly identify podocyte as a potentially important target for the renoprotective effects of 1,25(OH)2D3.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Recent reports indicate that 1,25(OH)2D3 can alleviate podocyte loss and inhibit podocyte hypertrophy in subtotally nephrectomized (SNX) rats (10). These results clearly identify podocyte as a potentially important target for the renoprotective effects of 1,25(OH)2D3.…”
Section: Introductionmentioning
confidence: 79%
“…Four weeks after injection, when proteinuria was stable, rats were randomly assigned into two groups: nephropathy group (NE, n=12), and nephropathy+1,25(OH)2D3 (ND, n=12), with matched body weight and urinary protein-to-creatinine ratio. Rats in ND group received 1,25(OH)2D3 treatment (3 ng/100 g body weight daily) through a subcutaneous osmotic minipump (10). Normal rats served as control group (NC, n=10).…”
Section: Establishment Of Experimental Nephropathy Modelmentioning
confidence: 99%
“…Moreover, beneficial effects of active vitamin D on progression of chronic kidney disease have been documented (13,19).…”
mentioning
confidence: 99%
“…Evidence shows that pleitropic effects of vitamin D go beyond bone and mineral metabolism and the activity of parathyroid glands, thus being possibly related to other potential areas of CKD. It has been demonstrated that vitamin D supplementation has an antiproteinuric effect, 33 to regulate the reninangiotensin-aldosterone, 34 , to reduce histological changes found in glomerulosclerosis, 35 , and, finally, to reduce CKD progression. 4 To sum up even if our population with CKD is in a tropical environment, which leads to more exposure to the sun and, consequently, a higher production and serum levels of 25(OH)D, our study showed that most analyzed patients had serum levels of 25(OH)D below recommended values, especially lower among women and in patients with larger abdominal circumference.…”
Section: Discussionmentioning
confidence: 99%